A web of orixás: Technology and the transmission of Candomblé songs in Bahia and Berlin - Graeff, Nina (Revista EntreRios do Programa de Pós-Graduação em Antropologia, 2020)
This paper draws upon ethnographic field research on the transmission of the Afro-Brazilian religion of Candomblé in two contrastive contexts: Recôncavo da Bahia and Berlin. Whereas in the religion’s original region, Bahia, people are immersed in what can be considered a universe of orixás – Candomblé’s West-African deities –, in Germany, a country with almost no references of the tradition, a context must be created for its practice. In this sense, technology, and especially the internet, should facilitate the transmission of Candomblé by displaying cultural references, from videos of rituals to lyrics of orixás songs, and connecting migrants and foreigners to its symbology, myths, songs and dances despite the physical distance from Brazil. Paradoxically, although in Bahia technology is considered an additional tool for learning, in Berlin, where references lack, it is a kind of taboo, bringing about controversies in the transmission of knowledge. While unveiling different modes of learning Candomblé’s bodily knowledge, this paper seeks to demonstrate through this paradox the intricacies of practical learning as well as of the interrelation between practice and discourse.